2021
DOI: 10.1136/bmjopen-2021-054039
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of chronic hepatitis B virus infection in Rwandan high-risk groups: unexpected findings on prevalence and its determinants

Abstract: ObjectivesUsing secondary data from 208 079 Rwandans, we determined the prevalence of chronic hepatitis B virus (HBV) infection among high-risk groups and its demographic, geographical and health-related determinants.DesignIn this cross-sectional study, we obtained and analysed data from a national hepatitis B vaccination and screening campaign conducted in Rwanda in 2017. We performed logistic regression to examine associations between chronic HBV infection and related factors such as risk status and geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…It is noteworthy that the sample size of this study was smaller as compared to those of the Ghana and Nigeria studies cited [ 19 , 20 , 21 ]. In general, however, the HBV prevalence in Liberia may be truly lower, but it was higher when compared with the prevalence from similar studies conducted in Rwanda or India, which reported a prevalence of 4.3% [ 23 ] and 8% [ 24 ], respectively. Furthermore, an extremely low prevalence of 0.9% has been reported among jail inmates in the USA [ 15 ], which could be attributed to the institutionalized measures of infection prevention and control programs besides the other interventions in place in American correctional facilities [ 25 ].…”
Section: Discussionmentioning
confidence: 63%
“…It is noteworthy that the sample size of this study was smaller as compared to those of the Ghana and Nigeria studies cited [ 19 , 20 , 21 ]. In general, however, the HBV prevalence in Liberia may be truly lower, but it was higher when compared with the prevalence from similar studies conducted in Rwanda or India, which reported a prevalence of 4.3% [ 23 ] and 8% [ 24 ], respectively. Furthermore, an extremely low prevalence of 0.9% has been reported among jail inmates in the USA [ 15 ], which could be attributed to the institutionalized measures of infection prevention and control programs besides the other interventions in place in American correctional facilities [ 25 ].…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, because NCD patients are already in regular contact with the healthcare system, they may be more easily mobilized for screening and linkage to treatment compared to other high-risk populations. Although Rwanda has conducted limited targeted screening among people living with human immunode ciency virus(HIV), pregnant women(8, 19),prisoners, sex workers, injection drug users, and men who have sex with men(MSM) (20), NCD patients are not currently targeted for hepatitis screening by the national Rwandan hepatitis program. In this context, our team implemented a targeted HBV and HCV screening among patients with NCDs in rural setting.…”
Section: Introductionmentioning
confidence: 99%